2012
DOI: 10.1111/j.1365-2044.2011.06981.x
|View full text |Cite
|
Sign up to set email alerts
|

The precision of PiCCO®measurements in hypothermic post‐cardiac arrest patients

Abstract: SummaryThe aim of the present study was to determine the precision of the PiCCO Ò system for post-cardiac arrest patients who underwent therapeutic hypothermia. The precision of the measurements for cardiac output, global end-diastolic volume, extravascular lung water and the pulmonary vascular permeability index was assessed using the least significant change; this was regarded as precise when less than 15%. A total of 462 measurement sets were prospectively performed on 88 patients following successful resus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 39 publications
2
28
0
1
Order By: Relevance
“…The principal of correct patient positioning is applicable to all anaesthesia procedures and is not limited to laryngoscopy [1]. I agree with Al-Jadidi et al [2] and El-Orbany et al [3] that, during direct laryngoscopy, appropriate head and neck position is essential to acquire optimum alignment and view of the glottis.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…The principal of correct patient positioning is applicable to all anaesthesia procedures and is not limited to laryngoscopy [1]. I agree with Al-Jadidi et al [2] and El-Orbany et al [3] that, during direct laryngoscopy, appropriate head and neck position is essential to acquire optimum alignment and view of the glottis.…”
supporting
confidence: 67%
“…Distractions during critical phases of anaesthesia such as induction have a detrimental effect on clinicians' performance, and increase the chance of an error, supporting the concept of a 'sterile cockpit' in anaesthetic practice [1]. Auditory alarms are known to attract attention more quickly and reliably than visual signals, but multiple similar alarms can create confusion [2].…”
Section: Equipment Manufacturers Must Differentiate Auditory Alarms Fmentioning
confidence: 99%
“…However, if necessary, a colder or higher volume bolus can be tried in order to obtain a ΔT° > 0.2°C. Tagami et al performed TPTD in patients under therapeutic hypothermia and found that the measurements were not only feasible but also precise [65,66].…”
Section: Step 9 Check δT°mentioning
confidence: 99%
“…Its additive advantage is the possibility to measure dynamic variables in fluid management. Tagami et al validated this method in post-cardiac arrest patients even if therapeutic hypothermia (32-34°C) was used [57].…”
Section: Transpulmonary Thermodilution Devices Like Picco™ (Pulse Indmentioning
confidence: 99%